2006
DOI: 10.1128/jvi.01207-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel 5′ Subgenomic RNA3a Derived from RNA3 of Brome Mosaic Bromovirus

Abstract: The synthesis of 3 subgenomic RNA4 (sgRNA4) by initiation from an internal sg promoter in the RNA3 segment was first described for Brome mosaic bromovirus (BMV), a model tripartite positive-sense RNA virus (W. A. Miller, T. W. Dreher, and T. C. Hall, Nature 313: [68][69][70] 1985). In this work, we describe a novel 5 sgRNA of BMV (sgRNA3a) that we propose arises by premature internal termination and that encapsidates in BMV virions. Cloning and sequencing revealed that, unlike any other BMV RNA segment, sgRNA3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 70 publications
0
16
0
2
Order By: Relevance
“…Sgp core hairpin was shown to act as a landing pad for RdRp during de novo initiation of sgRNA4 synthesis (2,145). Additionally, the sgp region leads to the formation of the 5 sgRNA3a (147). A recent study confirmed the high efficiency of the sgRNA3a-mediated homologous crossovers with BMV RNA3 (Figure 5a) (131).…”
Section: Cis-acting Replication Signal (Re): a 150-nt Subset Of The Bmentioning
confidence: 89%
“…Sgp core hairpin was shown to act as a landing pad for RdRp during de novo initiation of sgRNA4 synthesis (2,145). Additionally, the sgp region leads to the formation of the 5 sgRNA3a (147). A recent study confirmed the high efficiency of the sgRNA3a-mediated homologous crossovers with BMV RNA3 (Figure 5a) (131).…”
Section: Cis-acting Replication Signal (Re): a 150-nt Subset Of The Bmentioning
confidence: 89%
“…The RNAs were identified in Northern blots treated with a riboprobe that recognizes the conserved 3= UTR of the BMV RNAs. Bands identified by the asterisks likely correspond to prematurely terminated RNA2 and/or degradation products (37). The relative amounts of the four full-length BMV RNAs within each sample are quantified below the image of the Northern blots.…”
Section: Discussionmentioning
confidence: 99%
“…The fulllength BMV RNAs were identified by RNAs extracted from WT BMV virions. The bands highlighted with asterisks likely correspond to prematurely terminated RNA3 (37). (C) Quantification of the accumulation of plus-strand BMV RNA1 and RNA2 over time.…”
Section: Fig 6 Bmv Rna1 Accumulated To Higher Levels Than Bmv Rna2 Eamentioning
confidence: 99%
“…In order to synthesize sgRNA4, the replicase enzyme recognizes the core promoter sequence by an induced-fit mechanism (115). Recently, a novel 5Ј sgRNA3a in BMV that arose by premature termination of genomic RNA3 synthesis has been discovered (132). Studies with barley and A. thaliana protoplasts have shown that both the length of the oligo(A) tract and the stability of the sgp core hairpin affected sgRNA3a synthesis (J. Sztuba-Solińska and J. J. Bujarski, unpublished data).…”
Section: Transcription Of Sgrnamentioning
confidence: 99%
“…4. Two models of the crossing-over mechanism within the sgp region (27,132). The top part shows the organization of sgp, while the sgp sequence is shown on the bottom.…”
Section: Genetic Recombination Of Bromoviridaementioning
confidence: 99%